PERANAN AUDIT INTERNAL TERHADAP PENINGKATAN LAYANAN JASA PADA PT. TAC - Dira Ayu Hemania (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2025)
This study examines the role and effectiveness of internal audit in improving service quality at PT. TAC, an event organizer company. The main focus of the research is to identify operational problems that hinder the implementation of services, as well as how the client's perception of service quality and the role of internal audit in the process of evaluating and improving services. The location of the research is at PT. The seven Asta Creativa in the sample consisted of an operational manager, an event project manager, and two of the company's regular clients. The research method uses a qualitative approach with in-depth interview techniques and document analysis. The results of the study show that internal audits have so far focused more on administrative and compliance aspects, so they have not been able to handle the constraints of coordination between divisions and comprehensive service evaluation. Clients assessed that there was a discrepancy between the concept and the implementation of the event, as well as the lack of feedback mechanisms that directly involved them. This study recommends strengthening the internal audit function through expanding the scope of operational evaluation, developing an audit-based post-event evaluation system, training internal auditors in service risk management, and integrating audits with the company's quality management system. The implications of this research make an important contribution to the management of service quality in the event organizer industry with a more strategic and participatory internal audit approach.